Second Five Year Plan (1956-57 to 1960-61) Chanda District Bombay State - Planning Commission (Planning Commission, 1958)
Chanda District is situated between 20° 25' and 17° 56' North latitude and 80° 59' and 78° 48' East longitude. Formerly, it formed part of the Southern portion of the old Madhya Pradesh. Consequent to the re-organisation of the State, this District has been joined to the new Bombay State from 1st November, 1956. It forms the boundary on the extreme eastern portion of the new Bombay State. To the North, it is bordered by Wardha, Nagpur and Bhandara Districts, to the South by the Andhra State, to the East by Durg and Bastar Districts of the new Madhya Pradesh State and the whole of the Western border of the District is uninterruptedly bounded by Wardha, Pranhita and Godavari rivers.
Bombay State